Lecture Notes in Computer Science
DOI: 10.1007/978-3-540-71605-1_19
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Prime Numbers Using Cartesian Genetic Programming

Abstract: Abstract. Prime generating polynomial functions are known that can produce sequences of prime numbers (e.g. Euler polynomials). However, polynomials which produce consecutive prime numbers are much more difficult to obtain. In this paper, we propose approaches for both these problems. The first uses Cartesian Genetic Programming (CGP) to directly evolve integer based prime-prediction mathematical formulae. The second uses multi-chromosome CGP to evolve a digital circuit, which represents a polynomial. We evolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Mackey-Glass Chaotic Time Series [35] 8 Y N Y N Sunspot Prediction [27] 12 Y N Y N Financial Trading [6,13] 75-273 Y N Y Y Prime Number Prediction [66] 1 Y N Y N Drug Bioavailability [57] 241 Y N Y N Median Oral Lethal Dose [2] 626 Y N Y N Time Series Forecasting [65] 12-240 Y N Y N…”
Section: Predictive Modellingmentioning
confidence: 99%
“…Mackey-Glass Chaotic Time Series [35] 8 Y N Y N Sunspot Prediction [27] 12 Y N Y N Financial Trading [6,13] 75-273 Y N Y Y Prime Number Prediction [66] 1 Y N Y N Drug Bioavailability [57] 241 Y N Y N Median Oral Lethal Dose [2] 626 Y N Y N Time Series Forecasting [65] 12-240 Y N Y N…”
Section: Predictive Modellingmentioning
confidence: 99%
“…There was again support for signal processing, algorithmic and synthetic problems. Other suggested problems rarely mentioned elsewhere included prime number prediction [52] and real-valued optimization. One respondent recommended Boolean problems, but suggested that better ones than the typical parity and multiplexer problems were required, such as the multiple output parallel multiplier [53].…”
Section: Composition Of a New Benchmark Suitementioning
confidence: 99%
“…• The prime generating polynomial problem where the goal is to discover a polynomial that generates as many different primes in a row as possible. Cartesian Genetic Programming has also been applied to the problem of finding polynomials that generate prime numbers [21].…”
Section: Monte Carlo Expression Discoverymentioning
confidence: 99%